Ambiguità del petrarchismo Un percorso fra trattati d'amore, lettere e templi di rime - Favaro, Maiko (Critica Letteraria e Linguistica, 2021)
The volume draws attention to some elements of ambiguity in the Italian Petrarchism of the 16th century, with insights also into the early 17th century. In particular, the book analyses: the debate on some contradictory or at least problematic aspects of Petrarch's statements on love; the tension between literary artificiality and ostentation of sincerity in love letters; the ambiguity between sacred and profane in the encomiastic field, with special reference to the metaphor of the 'temple' in the so-called 'temples of poems'. The path here proposed offers an idea of Petrarchism as a phenomenon less rigid and stereotyped than usually perceived. Its ambiguities or even contradictions can be subjects of debate, without necessarily taking the path of anti-petrarchism and parodic deformation.